Impact of Childhood Trauma History and Self-Compassion on the Cosmetic Surgery Acceptance in Women of Reproductive Age: A Cross Sectional Study - Temiz, Mehtap (Springer, 2026)
AimCosmetic surgery is increasingly common among women of reproductive age, yet psychosocial determinants remain understudied. This study aimed to investigate the effects of childhood trauma and self-compassion on cosmetic surgery acceptance in women, with a focus on emotional and psychological influences shaping body image and surgical motivations.MethodThis cross sectional study was conducted online between June and September 2025. The sample consisted of 403 women aged 18-49 years. Data were collected with a Personal Information Form, the Childhood Trauma Scale, the Self-Compassion Scale-Short Form, and the Cosmetic Surgery Acceptance Scale. Statistical analyses included descriptive statistics, t test, ANOVA, Pearson correlation, and hierarchical regression.ResultsThe mean score for cosmetic surgery acceptance was 53.49 +/- 22.33, reflecting a moderate level among participants. Cosmetic surgery acceptance was negatively associated with self-compassion and positively associated with childhood trauma. Hierarchical regression analysis showed that these variables, along with the history of medical aesthetic procedures and cosmetic surgery, significantly predicted cosmetic surgery acceptance, explaining 46% of the variance.ConclusionChildhood traumas, particularly emotional abuse and neglect, were associated with higher levels of cosmetic surgery acceptance, while self-compassion showed a negative association with susceptibility to cosmetic surgery. Additionally, women with prior surgical or aesthetic experiences reported greater acceptance. These findings highlight the importance of integrating psychosocial screening into cosmetic surgery practice and promoting self-compassion in preoperative counseling to enhance patient well-being.Level of Evidence IVThis journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
Keywords: Acceptance; Childhood trauma; Cosmetic surgery; Self-compassion; Women